Differential involvement of serotonin and dopamine systems in cost-benefit decisions about delay or effort. - Denk, F; Walton, M; Jennings, K; Sharp, T; Rushworth, M; Bannerman, D (2005)
RATIONALE: Although tasks assessing the role of dopamine in effort-reward decisions are similar to those concerned with the role of serotonin in impulsive choice in that both require analysis of the costs and benefits of possible actions, they have never been directly compared. OBJECTIVES: This study investigated the involvement of serotonin and dopamine in two cost-benefit paradigms, one in which the cost was delay and the other in which it was physical effort. METHODS: Sixteen rats were trained on a T-maze task in which they chose between high and low reward arms. In one version, the high reward arm was obstructed by a barrier, in the other, delivery of the high reward was delayed by 15 s. Serotonin and dopamine function were manipulated using systemic pCPA and haloperidol injections, respectively. RESULTS: Haloperidol-treated rats were less inclined either to exert more effort or to countenance a delay for a higher reward. pCPA had no effect on the performance of the rats on the effortful task, but significantly increased the rats' preference for an immediate but smaller reward. All animals (drug treated and controls) chose the high reward arm on the majority of trials when the delay or effort costs were matched in both high and low reward arms. CONCLUSION: A dissociation was found between the neurotransmitter systems involved in different types of cost-benefit decision making. While dopaminergic systems were required for decisions about both effort and delay, serotonergic systems were only needed for the latter.